2021
DOI: 10.3389/fimmu.2021.801811
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I and MDA5 Protect Mice From Pichinde Virus Infection by Controlling Viral Replication and Regulating Immune Responses to the Infection

Abstract: RIG-I and MDA5 are major cytoplasmic innate-immune sensor proteins that recognize aberrant double-stranded RNAs generated during virus infection to activate type 1 interferon (IFN-I) and IFN-stimulated gene (ISG) expressions to control virus infection. The roles of RIG-I and MDA5 in controlling replication of Pichinde virus (PICV), a mammarenavirus, in mice have not been examined. Here, we showed that MDA5 single knockout (SKO) and RIG-I/MDA5 double knockout (DKO) mice are highly susceptible to PICV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…PICV is considered non-pathogenic as there are no known PICV-associated diseases in humans or other animals [34]. The virus can infect a wide range of cell types from diverse host animal species that may include but are not necessarily limited to human, mouse, monkey, and avian species [34][35][36][37]. The wide host ranges and avirulent nature of PICV makes it a promising viral vector for flexible delivery of vaccine immunogens in humans and various animal species.…”
Section: Introductionmentioning
confidence: 99%
“…PICV is considered non-pathogenic as there are no known PICV-associated diseases in humans or other animals [34]. The virus can infect a wide range of cell types from diverse host animal species that may include but are not necessarily limited to human, mouse, monkey, and avian species [34][35][36][37]. The wide host ranges and avirulent nature of PICV makes it a promising viral vector for flexible delivery of vaccine immunogens in humans and various animal species.…”
Section: Introductionmentioning
confidence: 99%
“…Mda5-deficient mice exhibited a selectively impaired response to several viruses including encephalomyocarditis picornavirus [9,10], norovirus-1 [11], paramyxoviri-dae [12,13], Theiler's encephalomyelitis virus [14], acute lymphocytic choriomeningitis virus [15], or Pichinde virus [16]. Interestingly, the absence of Mda5 protects mice from malaria plasmodium yoelii [17].…”
Section: Introductionmentioning
confidence: 99%
“…This cross-reactivity of T-cell mediated immunity to different lineages of LASV thus implies a significant functional level of adaptive cellular immunity in spite of the immunosuppressive effect during the early phase of the virus infection and suggests that high diversity among the different viral lineages does not necessarily abolish the putative conserved immune dominant T cell epitopes. It is noteworthy that we have recently shown that mice that lack the expression of one or both major cytosolic innate immune receptors (RIG-I and/or MDA5 knock out) can also exhibit a late but heightened level of adaptive (T-cell) immune responses to clear the infection by a prototypic arenavirus, called Pichinde virus (PICV), despite a defective level of innate immunity [ 55 ].…”
Section: Lasv Genomic Structure and Mechanisms Of Immune Responses To...mentioning
confidence: 99%